Emotion understanding during computer-supported collaboration - Xolocotzin Eligio, Ulises (2010)
Affect has been neglected in computer-supported collaborative learning, which is unfortunate because emotions play important roles in collaborative learning and human-computer interaction. This thesis investigated affect in co-located and remote remote-synchronous collaboration, answering the question: How does the task environment and interaction with a partner influence people’s emotions during computer-supported collaboration? In Study 1, the collaborative tasks and affective features of a game provoked more goal-oriented emotions (e.g., challenge) than an open task in a concept-mapping tool. In both environments individuals assumed emotional similarity with a partner, which not necessarily was true. Some partners that reported similar emotions also interacted positively (e.g., with responsiveness and coordination). Study 2 investigated the dynamics of challenge around a collaborative game. Challenge was likely to change when the task environment included features like complexity or required coordination. Challenge increased if partners struggled, and decreased if they performed fluently. Moreover, partners influenced each other’s actions in these situations. Probably this explained the similarity between partners’ reported challenge and their tendency to assume such similarity when reasoning about the emotions of each other. In any case, partners rarely discussed emotions during their collaborative interaction. Thus, Study 3 assessed the benefits of supporting affective awareness between partners during remote and co-located collaborations. Affective awareness facilitated enjoyable and productive interactions only during co-located collaborations, suggesting the remoteness highlighted the importance of an accurate understanding of a partner’s emotions, precipitating a more effective response to the demands of the task environment. The research shows that partners’ emotions are under the influence of one another’s actions, especially when the task environment requires them to solve collaborative tasks playing complementary roles. Moreover, collaborators assume emotional similarity with the partners. Thus, the process and outcome of collaboration might improve if the environment helps partners to have a better understanding of one another’s emotions.